Research on optimal control strategy for electric braking performance of urban rail vehicles - LIU Donghui; ZHAO Leiting; WANG Yongxiang; LIU Kan (机车电传动)
In light of the characteristics of frequent starting and stopping of urban rail transit vehicles, a control strategy was proposed for achieving precise stopping, enhancing ride comfort, reducing losses and saving energy through pure electric braking of asynchronous motors to zero speed. Within the full-speed range of vehicle operation, a dual-drive technology based on data and model was utilized to predict the maximum available deceleration of the vehicle. In the low-speed range of vehicle electric braking, a deceleration controller was designed to adjust the torque command value for motor braking in real-time. A discretized closed-loop full-order rotor flux observer was employed to identify the operating frequency of the motor, enabling the use of the identified frequency value to replace the frequency value collected by the speed sensor to complete the stopping process. Finally, the effectiveness of the above research strategy was validated through a hardware-in-the-loop simulation platform and vehicle operation tests.